Functional outcome of distal humerus fractures treated by orthogonal locking compression plating: a short-term study - Jeyarajan, Shivakumar; Loganathan, Dinesh (International Journal of Research in Orthopaedics, 2021)
Background: In Indian settings, the incidence of distal humeral fractures is associated with motor vehicle accidents and simple accidental falls. The treatment of these fractures continues to remain challenging due to anatomical factors. The present study was carried out to evaluate the functional outcome of distal humerus fractures treated with bicolumn locking compression plates applied orthogonally. Methods: This prospective study was carried out among 15 patients who were diagnosed with fracture of distal humerus. A detailed clinical examination and radiological assessment were done to evaluate the fracture pattern. In complex articular fractures, Chevron V shaped olecranon osteotomy was done. In other cases, routine approaches like TRAP, paratricipital or Triceps splitting approach were used. Results: The most common type of fracture observed was C2 (53.4%) and was associated with fracture of distal radius (26.6%) followed by fracture metacarpals (13.2%). Olecranon osteotomy was the most common surgical approach (40%). Majority of the participants in both the age groups equally showed excellent and good outcomes (42.8% and 37.5% respectively) while males showed excellent outcomes (55.6%) compared to females (16.7%). Conclusions: It is inferred that distal humerus fractures with intraarticular extension can be successfully treated with locking compression plates applied orthogonally. However, a long-term follow-up and a larger sample study is needed to further validate our findings.